Modeling Bainbridge-Ropers Syndrome in Xenopus laevis Embryos - Lichtig, Hava; Artamonov, Artyom; Polevoy, Hanna; Reid, Christine D.; Bielas, Stephanie L.; Frank, Dale (Frontiers in Physiology, 2020)
The Additional sex combs-like (ASXL1, ASXL3) genes are important genes linked to human neurodevelopmental disorders. The de novo truncating variants in ASXL1 and ASXL3 proteins serve as the genetic basis for severe neurodevelopmental diseases such as Bohring-Opitz and Bainbridge–Ropers syndromes, respectively. The phenotypes of these syndromes are similar but not identical, and include dramatic craniofacial defects, microcephaly, developmental delay, and severe intellectual disability, with a loss of speech and language. Bainbridge-Ropers syndrome resulting from ASXL3 gene mutations also includes features of autism spectrum disorder. Human genomic studies also identified missense ASXL3 variants associated with autism spectrum disorder, but lacking more severe Bainbridge-Ropers syndromic features. While these findings strongly implicate ASXL3 in mammalian brain development, its functions are not clearly understood. ASXL3 protein is a component of the polycomb deubiquitinase complex that removes mono-ubiquitin from Histone H2A. Dynamic chromatin modifications play important roles in the specification of cell fates during early neural patterning and development. In this study, we utilize the frog, Xenopus laevis as simpler and more accessible vertebrate neurodevelopmental model system to understand the embryological cause of Bainbridge-Ropers syndrome. We have found that ASXL3 protein knockdown during early embryo development highly perturbs early neural cell fate specification potentially resembling the Bainbridge-Ropers syndrome phenotype in humans. Thus, the frog embryo is a powerful tool for understanding the etiology of Bainbridge-Ropers syndrome in humans.